The aquaculture industry and opportunities for sustainable tourism - Faganel, Armand (Academica turistica, 2016)
Tourism is an important industry in the growth of gdp in many countries, while aquaculture covers more than half of the demand for fish in the developed world. The demand and competition for farmed fish are increasing worldwide, as is the awareness of the importance of the further development of sustainable small busi- ness. In this view, innovation is crucial to promoting sustainable business models that can achieve a solid economic performance and at the same time take care of the natural environment. This article contributes to the literature on sustainable business models with a descriptive case study of the complementarity of a single fish farming company and tourism activities. The case study of a sustainable business model in aquaculture has been analysed with the use of a business model canvas that links various market-oriented elements of a business model with different stakeholders' needs.
Keywords: blagovne znamke; sustainable development; tourism; trajnostni razvoj; turizem